Financial Feasibility Analysis of Gumanti Micro Hydro Power Plant Project - Muhammad, Aulia Rinald; Damayanti, Sylviana Maya (Journal of Business and Management, 2015)
Abstract - The limited electricity supply in Indonesia nowadays could results in condition where the social, economic growth in Indonesia is restrained. In Response, the government has created programs and policies regarding the electricity to encourage private sector to invest and build power plant development. PT. Sangriang Megasakti has the initiative to create a private micro hydro power plant named PLTM Gumanti. However, in order to establish the project, a feasibility analysis must be conducted in order to determine whether the project is feasible or not. Thus, this research is proposed to analyze the financial feasibility of Gumanti micro hydro project. In this case, research used financial tools in analyzing the project feasibility such as net present value, internal rate of return, payback period, profitability index, and economic value added. In calculating the tools and analyzing the results, several data of the project are required such as total capital expenditure of the project, the operational and maintenance expenditure, and the cash inflow from the electricity generated. The results from the financial feasibility analysis of the project are as follows: the net present value is IDR 45,606,095,418, the internal rate of return is 64%, the profitability index is 4.76, the payback period is 1 year 10 months, and the economic value added is IDR 21,705,617,081. The conclusion of the project is that project was good and feasible to develop. Moreover, the economic value added and rate of return shows that the project economically and financially are worth doing. As recommendation, the researcher recommends to create a letter of intent to conduct a good business and to negotiate the credit rate with the lenders, since the project has big rate of return and fast payback period.Â Keywords: Feasibility Study, Micro Hydro Power plant, Project analysis